Cost and carbon burden of long-acting injections: a sustainable evaluation. (June 2016) - Maughan, Daniel L.; Lillywhite, Rob; Cooke, Matthew
Abstract : Aims and method: This study explores the economic cost and carbon footprint associated with current patterns of prescribing long-term flupentixol decanoate long-acting injections. We conducted an analysis of prescription data from a mental health trust followed by economic and carbon cost projections using local and national data. Results: A reduction of £300 000 could be achieved across England by improving prescribing behaviour, which equates to £250 per patient per year and 170 000 kg CO2 e. These savings are unlikely to be released as cash from the service, but will lead to higher-value service provision at the same or lower cost. Most of these carbon emissions are attributable to the carbon footprint of the appointment – 88000 kg CO2 e (including energy use and materials used) and the overprescribing of medication – 66000kg CO2 e. Clinical implications: Psychiatrists need to review their prescribing practice of long-acting injections to reduce their impact on the National Health Service financial budget and the environment.